How do plants feel the heat and survive?. Issue 10 (October 2022) - Guihur, Anthony; Rebeaud, Mathieu E.; Goloubinoff, Pierre
Abstract : Climate change is increasingly affecting the quality of life of organisms on Earth. More frequent, extreme, and lengthy heat waves are contributing to the sixth mass extinction of complex life forms in the Earth's history. From an anthropocentric point of view, global warming is a major threat to human health because it also compromises crop yields and food security. Thus, achieving agricultural productivity under climate change calls for closer examination of the molecular mechanisms of heat-stress resistance in model and crop plants. This requires a better understanding of the mechanisms by which plant cells can sense rising temperatures and establish effective molecular defenses, such as molecular chaperones and thermoprotective metabolites, as reviewed here, to survive extreme diurnal variations in temperature and seasonal heat waves. Highlights: As the sun rises, the temperature rapidly increases and, by noon, heat may damage labile macromolecular complexes and impair the vital biological functions of plants. Plants have a heat shock response (HSR), which is activated via fluidity changes in the plasma membrane and heat-responsive cyclic nucleotide-gated ion channels (CNGCs), which use Ca 2+ and reactive oxygen species (ROS) as messengers to mediate a signaling pathway, leading to the upregulation of heat-induced mRNA in minutes, and to the accumulation of protective heat shock proteins (HSPs) and metabolites in hours. While some studies have been conducted on plant molecular chaperones, their precise role in acquired thermotolerance and the identity of their thermolabile protein substrates remain unknown. Based on 'omics analyses, plant HSR is a multigenic trait and new thermoresistant crops should harbor complementary mechanisms combining HSP chaperones and enzymes producing thermo- and ROS-protecting metabolites.